2014
DOI: 10.1161/hypertensionaha.113.02360
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Is Associated With Increased Pulmonary Artery Systolic Pressure in Humans

Abstract: Oxidative stress contributes to the development of pulmonary hypertension in experimental models, but this association in humans is unknown. We investigated the relationship between pulmonary artery systolic pressure measured by echocardiography and plasma aminothiol oxidative stress markers, with the hypothesis that oxidative stress will be higher in those with pulmonary hypertension. A group of 347 patients aged 65±12 years from the Emory Cardiovascular Biobank underwent echocardiographic assessment of left … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(30 citation statements)
references
References 49 publications
0
30
0
Order By: Relevance
“…A recent study of 347 patients who received TTE revealed that pulmonary artery systolic pressure was correlated with the oxidative stress markers cysteine, mitral regurgitation, statin use, left ventricular ejection fraction and patient age (21). ROS promote smooth muscle contraction by triggering elevated cytosolic free Ca 2+ concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 347 patients who received TTE revealed that pulmonary artery systolic pressure was correlated with the oxidative stress markers cysteine, mitral regurgitation, statin use, left ventricular ejection fraction and patient age (21). ROS promote smooth muscle contraction by triggering elevated cytosolic free Ca 2+ concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there is clear evidence that ROS production is increased in patients with essential hypertension, renovascular hypertension, malignant hypertension, salt-sensitive hypertension, cyclosporine-induced hypertension, and preeclampsia. [63][64][65] Population-based observational studies reported an inverse relationship between plasma antioxidants and blood pressure, and clinical studies have shown that systolic and diastolic blood pressures correlate positively with biomarkers of oxidative stress (plasma TBARS and 8-epi-isoprostanes) and negatively with antioxidant levels in patients with hypertension. 66,67 Plasma levels of asymmetric dimethylarginine (endothelial NOS inhibitor) and the lipid peroxidation product of linoleic acid, 13-hydroxyoctadecadienoic acid, a marker of ROS production, were inversely correlated with microvascular endothelial dysfunction and elevated blood pressure in hypertensive patients.…”
Section: Evidence Supporting a Role For Ros And Oxidative Stress In Hmentioning
confidence: 99%
“…On the other hand, P-gp facilitates transmembrane intracellular transport of various toxins, de- creasing the intracellular concentration of toxic compounds (16). The role of inflammation and oxidative stress in PAH pathogenesis is supported by many studies (3)(4)(5)(30)(31)(32). Cytokines, growth factors and shear stress represent endogenous activators of NADPH (nicotinamide adenine dinucleotide phosphate oxidase), which is a molecular complex that generates ROS (2).…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary arterial hypertension (PAH) is a hemodynamic and pathophysiological condition with multiple etiologies characterized by chron-ic and progressive remodelling of small pulmonary arteries, resulting in increased pulmonary vascular resistance (PVR) (1). Evidence suggests that inflammation, nitrogen oxides and oxidative stress contribute to the development and progression of lesions in the pulmonary vasculature (2,3). The reactive oxygen species (ROS) are an important mediator of vascular tonus, their excess generation being involved in the pathogenesis of PAH (4,5).…”
Section: Introductionmentioning
confidence: 99%